1989
DOI: 10.1038/341660a0
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing in wheat mitochondria results in the conservation of protein sequences

Abstract: RNA editing is a process that results in the production of a messenger RNA with nucleotide sequences that differ from those of the template DNA, and provides another mechanism for modulating gene expression. The phenomenon was initially described in the mitochondria of protozoa. Here we report that RNA editing is also required for the correct expression of plant mitochondrial genes. It has previously been proposed that in plant mitochondria there is a departure from the universal genetic code, with CGG specify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
240
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(251 citation statements)
references
References 15 publications
4
240
1
2
Order By: Relevance
“…The functional consequences of RNA editing in plant mitochondria are less understood [3][4][5]. Recent results suggest that mRNA editing plays an important role for the production of functional proteins [6].…”
Section: Introductionmentioning
confidence: 99%
“…The functional consequences of RNA editing in plant mitochondria are less understood [3][4][5]. Recent results suggest that mRNA editing plays an important role for the production of functional proteins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although ADAR-mediated RNA editing is mechanistically very different from other types of editing in mitochondria and chloroplasts, they should have some parallel evolutionary rationale. In plants, it is suggested that RNA editing helps repair otherwise-deleterious genomic mutations (53)(54)(55)(56)(57). The ADAR-mediated RNA editing system is driven by genetic variation to maintain phylogenetic conservation, similar to plant mitochondrial RNA editing.…”
Section: Rna Editing and Genetic Variationmentioning
confidence: 99%
“…Despite the discovery of plant RNA editing more than 20 y ago (7)(8)(9), only some of the components of the plant editosome are known. Cis-elements needed for recognition of C targets are usually found within 30 nt of the C to be edited (10)(11)(12)(13).…”
mentioning
confidence: 99%